Implementation of Character Education at Muhammadiyah 5 Porong Elementary School During the Covid-19 Pandemic - Kiki Fitri Sutrami; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This article discusses the implementation of character education at SD Muhammadiyah 5 Porong. Currently, Indonesia or even in several other countries are facing a global problem, namely the corona virus outbreak. With this pandemic, the government made a PSBB policy, residents are expected to implement social distancing or maintain a distance to stop the spread of the virus, schools, workplaces, places of worship are enforced by WFH or commonly known as Work From Home. This makes the world of education feel the impact of this pandemic, schools are closed and online learning is carried out at each student's home.The method that the author uses in digging and collecting this information is by direct observation to the location where to dig up information and conducting interviews with one of the educators at SD Muhammadiyah 5 Porong. The results of the research that the author has done, the author can draw important points contained in it, namely during the COVID-19 pandemic, namely the moral values contained in learning, character building through online learning, and learning carried out online must contain education. character and form the noble character of students.